Design and experiment analysis of the small maize harvester with attitude adjustment in the hilly and mountainous areas of China - Chen, Meizhou; Xu, Guangfei; Wei, Yuanzhen; Zhang, Yinping; Diao, Peisong; Pang, Huanxiao (International Journal of Agricultural and Biological Engineering, 2024)
To solve the problem of small planting plots and large sloping land for mechanized maize harvesting in China hilly and mountainous areas, a small maize harvester with attitude adjustment was designed to realize maize snapping, peeling, straw crushing and attitude adjusting at on time in this study. The basic structure and working principle of the small maize harvester were described, and the key components were designed as follows. The maize snapping device adopted the combination form of maize snapping plates and straw pulling rollers, and the gap of the straw pulling rollers can be adjusted to adapt to different maize varieties. Two pairs of peeling rollers formed a groove arrangement to improve peeling rate and reduced ear grain loss. The pressure feeding device mainly comprised drive chain and three grade pressure feeding rollers to increase the friction between ears and the peeling rollers, and help ears slide. The attitude adjustment advice was designed according to the high point stationary pursuit leveling method. When the attitude angle of the rack approached 0, the small maize harvester reached the level state. The actual range of attitude adjustment was obtained and the accuracy of static attitude adjustment was verified through attitude adjustment test. The influencing factors of ear loss rate and bract peeling rate were determined by orthogonal test, including the rotational speed of straw pulling rollers, peeling rollers and pressure feeding rollers. The mathematical regression model between the experimental factors and indicators was established by using Design Expert, and through the analysis variance to verify the significance of the evaluation indicators, the best combination of operation parameters was determined that the rotational speed of straw pulling rollers, peeling rollers and pressure feeding rollers were 1440 r/min, 1535 r/min and 406 r/min. Under the optimal combination of the operation parameters, the ear loss rate and bract peeling rate were 1.33% and 93.98%. The design indicators of the small maize harvester can meet the relevant national standards, and can satisfy the need of maize mechanized harvesting in China hilly and mountainous areas. Keywords: maize, harvester, hilly and mountains areas, attitude adjustment, anti rollover structureDOI: 10.25165/j.ijabe.20241701.7596Citation: Chen M Z, Xu G F, Wei Y Z, Zhang Y P, Diao P S, Pang H X. Design and experiment analysis of the small maize harvester with attitude adjustment in the hilly and mountainous areas of China. Int J Agric & Biol Eng, 2024; 17(1): 118-127.